Diode Laser and Calcium Hydroxide for Elimination of Enterococcus Faecalis in Root Canal - Neda Naghavi; Armita Rouhani; Sahar Irani; Nadia Naghavi; Elham Banihashemi (Mashhad University of Medical Sciences, 2014)
Introduction: The ultimate goal of endodontic treatment is to eliminate the bacterial infection in the root canal system. While mechanical debridement combined with chemical irrigation removes the bulk of microorganisms, residual bacteria are readily detectable in approximately one-half of teeth just prior to obturation. Laser light can be used to destroy bacteria. This in vitro study was performed to evaluate the effect of diode laser and calcium hydroxide on mono-infected dental canals.Methods: Fifty five single-rooted human premolars were prepared and contaminated with Enterococcus faecalis. After three weeks of incubation, the samples were divided into three experimental groups (n = 15) and two control groups (n = 5). In the first and second groups, the teeth were rinsed for 5 min with either sterile saline or 5.25% NaOCl and irradiated with a 810-nm diode laser at 1.5 W output for 5 × 4s. In the third group, the teeth were rinsed with 5.25% NaOCl and then Ca(OH)2 paste was inserted in the canals for 1 week. Intracanal bacterial sampling was done and the samples were plated to determine the CFU count. Results: 5.25% NaOCl plus laser was as effective as calcium hydroxide and significantly more effective than sterile saline (P>0.05) in elimination of E. faecalis. Complete elimination of E. faecalis was seen only for the one week calcium hydroxide treatment. Conclusion: Combination therapy with NaOCl irrigation and diode laser irradiation can be recommended as an effective treatment option for elimination of E. faecalis from the root canal system.